Plesionika alcocki ... - Chakraborty, Rekha Devi (Zenodo, 2021)
4.1 Plesionika alcocki (Anderson, 1896) – Fig 1 Pandalus alcocki — Anderson, 1896:92 [type-locality: Laccadive Sea off Malabar Coast of India; 9°34'57"N 75°36'30"E; 743 meters]. Pandalus (Plesionika) alcocki — Alcock and McArdle, 1901, pi. 52: figs. 2, 4. Plesionika alcocki: De Man, 1920: 105; Balss, 1925: 278, fig. 48; Mohamed and Suseelan, 1973; Chace, 1985: 55; Hayashi, 1986: 127, 270, fig. 81; Kensley, Tranter & Griffin, 1987: 313; Dave, 2002: 347; Fransen, 2006: 62-65, fig.17. Material examined: India, Tamil Nadu, Tuticorin fishing port, fishing off Bay of Bengal, 8°47′40"N, 78°09'37"E, 200- 300 m, Jan 2015, 3 males CL 22-25 mm, (CMFRI). 4.2 Plesionika narval (Fabricius, 1787) – Fig 2 (a-k) Astacus narval Fabricius, 1787: 331 (type locality: probably Nice, Mediterranean). Description: Rostrum armed dorsally with 4-6 teeth, ventrally armed with 8-23 teeth becoming obscure anteriorly; orbital margin rather regularly concave; abdomen without posteromesial tooth or median dorsal carinae on 3 rd somite, ... : Published as part of Chakraborty, Rekha Devi, 2021, Notes on Plesionika alcocki (Anderson, 1896) and Plesionika narval (Fabricius, 1787) from the southern coast of India, pp. 281-287 in International Journal of Fisheries and Aquatic Studies 9 (1) on pages 282-283, DOI: 10.22271/fish.2021.v9.i1d.2412, http://zenodo.org/record/12550451 ...